Answers:
1.) [tex]\bold{y=5}[/tex]
2.) [tex]\bold{y=3}[/tex]
3.) [tex]\bold{y=1}[/tex]
4.) [tex]\bold{y=-1}[/tex]
Solution Steps:
______________________________
1.) To figure out y, you have to plug in the x value into the equation given:
[tex]y=-2(-1)+3[/tex]
- Multiply −2 and −1 to get 2.
2.) To figure out y, you have to plug in the x value into the equation given:
[tex]y=-2(0)+3[/tex]
- Multiply −2 and 0 to get 0.
3.) To figure out y, you have to plug in the x value into the equation given:
[tex]y=-2(1)+3[/tex]
- Multiply −2 and 1 to get −2.
4.) To figure out y, you have to plug in the x value into the equation given:
[tex]y=-2(2)+3[/tex]
- Multiply −2 and 2 to get −4.
______________________________